2008
DOI: 10.1021/ja0739234
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Reverse Micelles in Supercritical CO2 Entrap Protein in Native State

Abstract: Molecular dynamics simulations of random quaternary mixtures of protein-water-CO2-fluorosurfactants show the self-assembly of reverse micelles in supercritical carbon dioxide where the protein becomes entrapped inside the aqueous pool. Analyses show that the protein native state remains intact in the water pool. This is because of the bulk nature of the enclosed water that provides a suitable environment for the extracted protein. Results from ab initio calculations imply that the existing fluorosurfactants ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Therefore, observing the behavior of ∆G # and ∆E # and comparing them with literature data, it can be stated that the immobilized lipase treated with SC-CO 2 in this work is less stable than those obtained by other works with lipases [25,44,45]. This instability was described by many researches through molecular dynamic simulation [33,38,46,47].…”
Section: Data Onsupporting
confidence: 52%
“…Therefore, observing the behavior of ∆G # and ∆E # and comparing them with literature data, it can be stated that the immobilized lipase treated with SC-CO 2 in this work is less stable than those obtained by other works with lipases [25,44,45]. This instability was described by many researches through molecular dynamic simulation [33,38,46,47].…”
Section: Data Onsupporting
confidence: 52%
“…24,[40][41][42] Marchi and co-workers used explicit molecular dynamics (MD) simulations to study the structure and dynamics of an AOT/H 2 O/isooctane RM assembly. 40 They found that the RMs did not retain a spherical shape.…”
Section: B the Nature Of A Reverse Micelle Environment In Peptide Comentioning
confidence: 99%
“…The presence of a bulklike core for RM radius comparable to and larger than w 0 ) 7.5 has important implications for the solvation of biomolecules in RMs. 15,76 As indicated by the intrinsic density profiles, the interfacial region within 10 Å from the headgroup sulfur atoms contains two well-defined peaks. The first peak corresponds to water molecules interacting directly with the headgroup and represents an outermost shell region.…”
Section: Discussionmentioning
confidence: 99%